Risk Factors Associated with End-Stage Renal Disease in Type 2 Diabetes Mellitus Patients - Putri, Suci Tuty (KnE Life Sciences, 2021)
Diabetes Mellitus is a chronic disease and has various complications, including diabetic nephropathy. This complaint is found in 20-40% of diabetes patients and a primary cause of end-stage renal disease. Identifying risk factors has an important role in the implementation of various health promotion and disease prevention activities. This research aims to know the risk factors which related to end-stage renal disease. This is an analytic descriptive study with a case control approach. The study involves 23 people in the test group and 46 in the control group. Bivariat analysis showed risk factors for end-stage renal disease are duration of DM (p-value:0.028), diet pattern (p-value: 0.000; OR: 13.5), hypertension (p-value: 0.036; OR: 2.9), smoking (p-value: 0.027; OR: 3.3), alcohol consumption (p-value: 0.034; OR: 0.3). While sex (p-value: 0.222), history of renal disease in the family (p-value: 0.09), activities (p-value: 0.149/0.457), dyslipidemia (p-value: 0.561) and HbA1